Publisher Correction: Graphene overcoats for ultra-high storage density magnetic media (Nature Communications, (2021), 12, 1, (2854), 10.1038/s41467-021-22687-y) - Dwivedi, N. (Nature Research, 2022)
10.1038/s41467-021-23869-4